OPTICAL CHARACTER RECOGNITION USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Musiał, Adam; Szczepaniak, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article represents results of the research of an Optical Character Recognition system. Proposed OCR system is able to convert a raster image into the text string, which represents the text shown on the input image. The main innovation is the fact that the system was created without following any strict rules. It was more an innovative research rather than simple programming using ready guidelines.